Identifying the Stance of Monetary Policy at the Zero Lower Bound: A Markov-Switching Estimation Exploiting Monetary-Fiscal Policy Interdependence - GONZALEZ-ASTUDILLO, MANUEL (Journal of money, credit and banking, 2018)
In this paper, I propose an econometric technique to estimate a Markov-switching Taylor rule subject to the zero lower bound of interest rates. I show that linking the switching of the Taylor rule coefficients to the switching of the coefficients of an auxiliary uncensored Markov-switching regression improves the identification of an otherwise unidentifiable prevalent monetary regime because of the presence of the zero lower bound. Using a Markov-switching fiscal policy rule as the auxiliary regression, I apply the estimation technique to U.S. data. Results show evidence of monetary and fiscal policy comovements, with monetary policy reacting weakly to inflation when fiscal policy is focused on real activity as opposed to debt stabilization, and vice versa.